KONDISI EKOLOGI MANGROVE DI PANTAI PUTRA DELI DESA DENAI KUALA KECAMATAN PANTAI LABU KABUPATEN DELI SERDANG PROVINSI SUMATERA UTARA The Ecological Condition of Mangrove in Putra Deli Beach, Denai Kuala Village, Pantai Labu Sub District, Deli Serdang Distr - Dinarta Hutabarat; Yunasfi Djayus; Ahmad Muhtadi (AQUACOASTMARINE, 2015)
Mangerove is the living plant community between the sea and the land that wasinfluenced by the tides. Putra Deli beach in Denai Kuala village, Pantai Labu Regency ofNorth Sumatera has an area of mangrove forest about 20 Ha. Putra Deli Beach still has anatural mangrove ecosystem. But, the coastal has long been used by the local community as asourceof livelihood especially mangrove orest logging. This research was aimed to know theecological condition of mangrove waters. This research is done in March 2015 till April 2015.This research is done with a purposive sampling method by taking and observing of bioticcomponents which was mangrove vegetation and density of Telescopium telescopium andthe measurement of water quality parameters. Data analysis included analysis of mangrovevegetation, analysis of water quality, analysis of substrate and analysisof morfometri leaves.There are 7 kinds of mangrove which found in the research location, namely Acrostichumspeciousum, Avicennia alba, Avicennia lanata, Avicennia marina, Bruguiera cylindrica,Lumnitzera littorea, and Rhizophora mucronata. Based the decision of environment ministernumbe 201/2004, the mangrove density in all of the stations included in category mediumand the mangrove cover included in category rarely. The kind of mangrove substrate at thisresearch is very solid. The condition of mangrove waters compared with the decision ofenvironment minister number 51/2004. The kind of mangrove substrate at the tis research isclays sand. Telescopium telescopium much found in station I. the biggest diversity index is inthe station I about 3.8.Keywords: Mangrove, The ecological condition, Water quality, T. telescopium